The effectiveness of vitamin C in the prevention and treatment of common cold: what is current evidence base? - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
To recommend taking vitamin C for common cold profilaxis or treatment is a common practice for physicians and healthcare professionals. But what is the evidence base?